Management And Handling Of Documented Information In Transportation Organizations, According To Ecuadorian Legal Provisions, An Analysis Of The Planning System (International Journal of Environmental Sciences, 2025)
An intervention model for a tariff-based rotational parking system is proposed, tailored to the contexts and best practices in cantonal head cities within the Andean region of Colombia, Ecuador, and Peru. Mechanisms and solutions are adopted that, on a smaller scale, cater to the need for vehicular organization in the critical historical zones or centers of cantonal head cities. This model addresses the knowledge gap resulting from the absence of specific experiences and studies that reflect the characteristics of cantonal head cities from an Andean perspective. It provides a flexible intervention proposal that allows each Cantonal Transport Directorate to apply it, considering the local context. The research uses a non-experimental, cross-sectional, and descriptive design, encompassing both explanatory and exploratory research types, in addition to case studies. The conclusion is drawn to disseminate this intervention model to the rest of the cantons in the Andean region, contributing to the positive development of local governance in each city.